Sex differences in the prevalence and correlates of emergency department utilization among adults with prescription opioid use disorder. (7th June 2019) - John, William S.; Wu, Li-Tzy
Abstract: Background: The emergency department (ED) is well-suited as an opportunity to increase treatment access for prescription opioid use disorder (POUD). We examined sex differences in ED utilization among individuals with POUD to understand potential sex-specific treatment barriers and needs. Methods: Data from the 2005–2014 National Surveys on Drug use and Health were analyzed to examine the prevalence and correlates of past-year ED utilization among male and female adults aged 18 or older with POUD ( n  = 4412). Results: Overall, 58.2% of adults with POUD reported past-year ED utilization. Adjusted logistic regression revealed that females (vs. males) with POUD were more likely to report past-year ED utilization. Among females with POUD, older age, lower income, obtaining opioids from a physician, major depressive episode, and greater POUD severity were associated with increased odds of ED utilization. Among males with POUD, public insurance and obtaining opioids from a physician were associated with ED utilization. A larger proportion of males with POUD reporting ED use had multiple substance use disorders than those with no ED use. Treatment history (lifetime or past-year) for alcohol, drugs, or opioid use was associated with increased odds of ED use among males and females with POUD. Conclusions/Importance: Males and females with POUD presenting to the ED may have distinct predisposing, enabling, and need-related correlates. Sex-specific screening and intervention strategies may be useful to maximize the utility of the ED to address POUD.